Nursing students facing moral distress: strategies of resistance - Simoní Saraiva Bordignon; Valéria Lerch Lunardi; Edison Luiz Barlem; Rosemary Silva da Silveira; Flávia Regina Ramos; Graziele de Lima Dalmolin; Jamila Geri Tomaschewski Barlem
ABSTRACT Objective: To understand the resistance strategies adopted by undergraduate students in nursing, faced with situations of moral distress (MD). Method: Qualitative research, developed in three universities in the south of Brazil, two federal and one private, with 21 undergraduate students in nursing from December 2015 to February 2016; the data was submitted to the discursive textual analysis and Foucauldian theoretical reference. Results: Students resisting demonstrate a sense of self-preservation and moral empowerment. Moreover, non-resistance initiatives are related to the fear of possible sanctions. Thus, by resisting or not, students may experience both positive and negative repercussions. Final considerations: By resisting, students aim to defend what they believe to be right, demonstrating their moral empowerment in the face of their moral distress. However, the exercise of disciplinary power seems to contribute to their moral fragilization, making it difficult to implement resistance strategies.